Associations between reversible and potentially reversible cognitive frailty and falls in community-dwelling older adults in China: a longitudinal study - Xiaonuo Xu; Ning Ding; Jing He; Ronghui Zhao; Weiqi Gu; Xiaoyan Ge; Kai Cui (BMC Geriatrics)
Abstract Background Few studies have focused on comparing the effect of cognitive frailty (CF) with either cognitive impairment or frailty alone on fall risk. Further, studies investigating the effect of reversible cognitive frailty (RCF) or potentially reversible cognitive frailty (PRCF) on fall risk are scarce. This study aimed to investigate the influence of RCF and PRCF on falls in community-dwelling older adults of China and determine whether CF conferred a higher risk than cognitive impairment or frailty alone. Methods This study used data from five waves of the China Health and Retirement Longitudinal Study (CHARLS) conducted from 2011 to 2020. A total of 3,200 participants were divided into six groups: Healthy, cognitive impairment [subjective cognitive decline (SCD) and mild cognitive impairment (MCI)], Frailty, and CF (RCF and PRCF), according to their baseline cognitive and frailty status. A generalized estimating equation was applied to measure the association of cognitive status, frailty, and CF with risk of falls. Multivariate logistic regression models were employed to analyze potential multiplicative and additive interactions of baseline cognitive impairment and frailty on fall risk. Results Of the 3,200 participants, 17.7% and 8.3% experienced falls and fall-induced injuries, respectively, in wave 2013. After adjusting for all covariates, the participants in the PRCF group [odds ratio (OR) = 1.442, 95% confidence interval (CI): 1.179–1.922] had a higher risk of falling than those in the RCF group (OR = 1.302, 95% CI: 1.053–1.593), while cognitive impairment alone or frailty alone were not associated with increased risk. The interaction analyses revealed a lack of multiplicative (OR = 0.952, 95% CI: 0.618–1.468) or additive [relative excess risk (RERI) =-0.043, 95% CI: -0.495–0.409; attributable proportion (AP) =-0.035, 95% CI: -0.400–0.329; synergy index (S) = 0.840, 95% CI: 0.172–4.095] interactions of cognitive impairment and frailty for falls. Conclusions We found that the risk of falls increased in RCF and PRCF compared to either cognitive impairment or frailty alone, with PRCF being associated with a higher risk than RCF. Clinical trial number Not applicable.